Digitization strategies in Argentine MSMEs: Is the level of commitment associated with digital maturity? - Jones, Carola; Alderete, María Verónica; Ascenzi, Laura; Davila Fialli, Elsi Esmeralda; Nuncira López, Gloria; Ladydo, Nicolás Leon (Papeles de Europa, 2025)
The study analyzes the commitment of Argentine MSMEs to the digitization strategy in a context of accelerated technological transformation. Using data from the Ibero-American Observatory of MSMEs (2022), an indicator is constructed that measures this commitment and its relationship with digital maturity, sector, and business size. The results reveal structural gaps and sectoral differences, as well as the influence of leadership and strategic planning on technology adoption. Useful evidence is provided for designing policies and programs that strengthen the digital capabilities and sustainable competitiveness of the MSME sector.
Keywords: digitalization; SMEs; strategic commitment